Optimization of effective communication skills in preparing social workers through interactive webinars [Optimalisasi keterampilan komunikasi efektif pada persiapan pekerja sosial melalui webinar interaktif] - Soulthoni, Hannin Pradita Nur; Wijayanti, Dewi Y (Universitas Syiah Kuala, 2025)
Students in the Social Welfare Science Program at Halu Oleo University face various challenges in developing communication skills, including low self-confidence, difficulty in active listening, and managing communication in complex situations. These obstacles can hinder their competencies as prospective professional social workers. This study aims to enhance students communication skills through webinar-based training that integrates theory and practice while evaluating its impact on four main aspects of communication skills. The training was conducted online using the Zoom platform, involving 73 students. Data were collected through pre-tests and post-test s to evaluate skill improvement using descriptive quantitative methods, while discussion and simulation results were qualitatively analyzed to complement the evaluation. The training showed significant improvement in all aspects of communication skills tested. An average increase of 30% was observed in understanding effective communication, self-confidence, active listening skills, and communication abilities in social case contexts, with active listening skills recording the highest increase of 28%. In conclusion, webinar-based training was effective in improving students communication competencies, demonstrating that integrating theory and simulation can bridge the gap between academic learning and practical application. Similar programs are recommended for integration into social education curricula and further research in more complex field contexts.